IMPACT ON THE EFFECTIVENESS OF MARKETING SERVICES IN HOTELS DETERMINING FACTORS AND THEIR DETERMINATION - Usmanova Dilfuza Ilkhomovna (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2023)
In this article, the attraction of tourists to our country, promotion to the international level, development of hotel service, development of private entrepreneurship, improvement of the quality of service and services were considered.